A rare case of aberrant quadriceps muscle anatomy preventing anterolateral thigh flap harvest. (March 2016) - Omakobia, Eugene; Liew, Colin; Berridge, Natasha; Cotrufo, Stefano
Abstract: The anterolateral thigh (ALT) flap is now widely established as a versatile flap which can provide ample amounts of skin, muscle and fascia to construct a variety of defects following major head and neck surgery. However, its use remains cautious due to well documented variations in its vascular anatomy for which this flap is notorious. What is less well known is the effect of variations in quadriceps muscle anatomy on the success of flap harvest. Here, we report a unique case in which fusion of the vastus intermedius (V.I) and vastus lateralis (V.L) muscles precluded ALT flap harvest. We also advise on appropriate management should similar cases be encountered. To our knowledge this is the first reported case of its kind in the English language literature.